An extramedullary plasmacytoma in the kidney of a 14-year-old girl: Case report and review of the literature. Issue 6 (February 2017) - Mei, Yan-hui; Yu, Jian-peng; Li, Gang
Abstract: Rationale: Extramedullary plasmacytoma (EMP) a rare plasma cell disorder and is frequently associated with plasma cell bone marrow infiltration. Most EMPs involve mucosal lymphoid tissue, especially in the nasopharyngeal area, respiratory tract, and head and neck region. Primary involvement of the kidney is exceedingly rare. Patient Concerns: A 14-year-old girl was admitted in our hospital with intermittent right upper quadrant pain for 1 month and recent (1 day) progressive deterioration. There was a mass found by ultrasonography in the right kidney and subsequent abdominal computed tomography scan revealed a 3 cm mass within the right kidney. Diagnoses: Pathology revealed typical histology of plasmacytoma and immunohistochemistry revealed the expression of CD138, CD45, vimentin, and Kappa light chain. Interventions: The patient successfully underwent radical nephrectomy with an uneventful recovery. She received no chemotherapy or radiotherapy after surgery. Outcomes: There was no recurrence or metastasis during a 22-month follow-up. Lessons: Our case study demonstrated that renal EMP with a relatively indolent clinical course, if detected at an early stage, can be treated by radical nephrectomy without adjuvant therapy. Generally, the clinical outcome and prognosis of EMP are favorable